Pendampingan Penggunaan Aplikasi Petadampot untuk Meningkatkan Pendidikan Keterampilan Hidup Siswa Sekolah Dasar - Kartika Yuni Purwanti; Suamanda Ika Novichasari; Zulmi Roestika Rini (Jurnal Pengabdian Masyarakat (abdira), 2021)
This service is aimed at Grade 4 students at SDN Jubelan 01, Sumowono District, Semarang Regency. The problems faced by partners are that students are not equipped with knowledge about life skills education, have not been empowered to grow vegetables and fruit in pots, and students' knowledge is only limited to planting plants in pots without paying attention to plant needs. The methods used are socialization, demonstration and practice as well as monitoring and evaluation. The results of this training activity participants have experienced an increase in PKH by an average of 92.17%, namely student knowledge about PKH 100%, knowledge about tabulampot 83.49%, student skills in planting tabulampot 93.76% and student knowledge about plant care 91.44%. Therefore, the results of this health literacy training activity can be said to be successful in the very good category. Petadampot media helps students in taking care of plants so that they can improve student survival education, especially in terms of food security. This activity is expected to be one of the school's flagship programs that can be a source of school income.